Performing under pressure in elite football - Jordet, G. (7th World Congress on Science and Football (WCSF), 2011, 2011)
The football (soccer) penalty shootout is used to identify a winner when two teams are tied in tournaments. Given that this event is known as a vast pressure situation where shooters typically are assumed to have an advantage over the keeper, the shooters` failure to live up to expectations of scoring may indicate that choking has taken place. In this presentation, multiple studies are presented that document different aspects of choking under pressure in international penalty shootouts. This includes data from indepth interviews with players who have taken part this event at the highest level; match record and video evidence from all penalty shootouts ever held in the World Cup, European Championships, and UEFA Champions League; and real-world interventions with teams participating in some of these tournaments. It is found that the results from these studies are consistent with a view of choking under pressure as related to favorable views of self under threat. Performers then underachieve when they engage in self-defeating self-regulation strategies initiated to escape the unpleasant affect associated with the pressure. The presentation is concluded with practical implications for practitioners in football.